Sugar water feeding practices are associated with bird species composition in urban backyards. Issue 1 (24th July 2021) - Erastova, Daria A; Galbraith, Josie A; Cain, Kristal E; van Heezik, Yolanda; Filion, Antoine; Stanley, Margaret C
Abstract: Feeding backyard birds with sugar water is increasingly popular in urban areas, but it has poorly understood effects on bird assemblages. In New Zealand, ca. 20% of households engaged in feeding wild birds use sugar water, often in an attempt to attract native, nectarivorous birds. Developing best practices for sugar water feeding could be a powerful tool for attracting these species in urban areas. However, it is currently unclear whether these feeders actually support native species, and, if so, which feeding practices are most effective in increasing visitation. We surveyed New Zealanders who provide sugar water to birds about their feeding practices via an online questionnaire. The aim of our research was to understand existing practices and their effect on attracting native species, as well as the motivations and social factors behind urban sugar water bird feeding. Our results show that this practice is popular throughout the country with the majority of households successful in attracting native nectarivorous species to their gardens. Sugar water feeder type had the largest effect on reported species richness at feeders in comparison to other factors (e.g. sugar concentration). Feeders specifically designed for nectarivorous birds, namely the Tui Nectar Feeder™, are more successful at attracting natives in comparison to other commonly used feeder types. Thus, individual householder decisions around feeder use can have important consequences for bird species composition in urban gardens. Future research is needed to understand the consequences of sugar water feeding for bird communities and individual bird health.